Мостовые магниточувствительные сенсоры - Vikulina, L. F.; Mingalev, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Designs have been developed for magnetically sensitive bridge sensors consisting either of four single-collector magnetotransistors or of a pair of dual-collector magnetotransistors with opposite conduction types. The sensitivity of these sensors is an order of magnitude higher than that of known sensors due to the fact that all elements of the bridge respond to the action of a magnetic field.